Perbandingan Latihan Pass and Follow Drill Circle dengan Pass and Follow Drill Square Terhadap Peningkatan Passing Pendek Pada Cabang Olahraga Sepak bola - Hendra Rustiawan; Andang Rohendi; Endi Rustandi; Adang Sudrazat (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
Short passing has a basic technique in soccer that must be mastered by every soccer player. The aim the research was studied the comparised of pass and follow drill circle and pass and follow drill square to increased short passing in soccer. The research method used was a experiment. The sampling technique was total sampling. The participants were students of Universitas Galuh Ciamis, Indonesia a count was 30 participants. The research instrument used was passing and stopping. The results was pass and follow drill circle and pass and follow drill square was significantly influence the to increased for short passing in soccer. But the exercise that had the biggest effect was the pass and follow drill square. The conclusion was that the pass and follow drill circle and the pass and follow drill square could be increased short passing in soccer.